Anaerobacillus alkaliphilus sp. nov., a novel alkaliphilic and moderately halophilic bacterium. Issue 3 (23rd January 2019) - Borsodi, Andrea K.; Aszalós, Júlia M.; Bihari, Péter; Nagy, István; Schumann, Peter; Spröer, Cathrin; Kovács, Attila L.; Bóka, Károly; Dobosy, Péter; Óvári, Mihály; Szili-Kovács, Tibor; Tóth, Erika
Abstract : Two alkaliphilic and moderately halophilic bacterial strains B16-10 T and Z23-18 characterized by optimal growth at pH 9.0–10.0 and 5 % (w/v) NaCl, were isolated from the rhizosphere soil of the bayonet grass ( Bolboschoenus maritimus ) in the Kiskunság National Park, Hungary. Cells of both strains stained Gram-positive, were motile straight rods, and formed terminal, ellipsoidal endospores with swollen sporangia. The isolates were facultative anaerobic, catalase positive, oxidase negative. Both strains contained meso -diaminopimelic acid as diagnostic diaminoacid of the peptidoglycan. Menaquinone-7 (MK-7) was the predominant isoprenoid quinone. Anteiso-C15 : 0, C16 : 1 ω11 c and iso-C14 : 0 were the major cellular fatty acids. The DNA G+C content of both strains was 35.8 mol%. The 16S rRNA gene based phylogenetic analysis revealed that the facultative anaerobic strains B16-10 T and Z23-18 showed the highest similarities to the type strains of anaerobic Anaerobacillus isosaccharinicus NB2006 T (98.7 and 99.1 %), A. macyae JMM-4 T (98.2 and 98.4 %), A. alkalidiazotrophicus MS 6 T (97.7 and 98.4 %), A. alkalilacustris Z-0521 T (97.5 and 98.3 %) and A. arseniciselenatis DSM 15340 T (97.5 and 98.2 %). However, the distinctive phenotypic and genetic results of this study confirmed that strains B16-10 T and Z23-18 represent a novel species, for which the name Anaerobacillus alkaliphilus sp. nov. is proposed. The type strain is B16-10 T (=DSM 29790 T =NCAIM B 02608 T ).